2006
DOI: 10.1111/j.1468-3083.2006.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical calcipotriol, betamethasone dipropionate and their combination in the treatment of localized vitiligo

Abstract: Combined therapy appeared to give a significantly faster onset of repigmentation along with better stability of the achieved pigmentation and with lesser number of side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…These findings were consistent with other studies like Kumaran et al and Parsad et al 15,16 A trial was conducted by Kumaran et al to evaluate the effect of topical calcipotriol ointment (0.005%) and betamethasone dipropionate (0.05%) cream, given alone or in combination, in treatment of localized vitiligo. Group I patients were treated with betamethasone dipropionate (0.05%) cream twice daily.…”
Section: Discussionsupporting
confidence: 80%
“…These findings were consistent with other studies like Kumaran et al and Parsad et al 15,16 A trial was conducted by Kumaran et al to evaluate the effect of topical calcipotriol ointment (0.005%) and betamethasone dipropionate (0.05%) cream, given alone or in combination, in treatment of localized vitiligo. Group I patients were treated with betamethasone dipropionate (0.05%) cream twice daily.…”
Section: Discussionsupporting
confidence: 80%
“…They also showed that this combination is able to minimize corticosteroid side effects (Kumaran et al, 2006). In other study, Travis and Siverberg revealed that calcipotriene in combination with corticosteroids could repigment vitiligenous lesions, even in those with previous treatment failure with corticosteroids (Travis & Siverberg, 2004).…”
Section: Suggested Guideline For Treatment Of Vitiligomentioning
confidence: 93%
“…Fluticasone propionate is the first carbothioate corticosteroids, classified as a potent, characterized by high lipophilicity, high glucocorticoid receptor binding and activation, and a rapid metabolic turnover in skin; thus, it has low cutaneous and systemic side effects, even in sensitive areas such as face, the eyelids and intertriginous regions (Kumaran, 2006). It seems that it can be a good treatment option for vitiligo.…”
Section: Place Of Corticosteroids In Treatment Of Vitiligomentioning
confidence: 99%
See 2 more Smart Citations